The Influence of Brand Ambassador on Consumer Purchase Decisions: A Study of Mie Sedaap Korean Spicy and K-Pop Enthusiasts in Bandung - Muhammad Riefla Gustiawan; Anny Nurbasari (PT. Global World Scientific, 2024)
The objective of this study is to determine and analyze the influence of the brand ambassador on purchase decisions. The research methods use quantitative with a descriptive and verificative approach. The sampling technique in this research uses purposive sampling. The sample for this study consists of 106 respondents who are over 17 years old, K-pop fans in Bandung and have purchased Mie Sedaap Korean Spicy. The results showed that the variables of brand ambassador and purchase decisions are in the good category. Furthermore, the brand ambassador has an influence on purchase decisions. And then, there is still needs improvement, especially when launching the new product. Consideration of launching new products in the future is expected to make consumers buy the product at the time of the product launch or close to the product launch date. With a successful product launch that convinces purchases, of course this will attract the attention of other potential consumers.